Wireshark & Ethereal network protocol analyzer toolkit - Orebaugh, Angela (Jay Beale's open source security series., 2007)
Ethereal is the #2 most popular open source security tool used by system administrators and security professionals. This all new book builds on the success of Syngress' best-selling book Ethereal Packet Sniffing. This book provides complete information and step-by-step Instructions for analyzing protocols and network traffic on Windows, Unix or Mac OS X networks. First, readers will learn about the types of sniffers available today and see the benefits of using Ethereal. Readers will then learn to install Ethereal in multiple environments including Windows, Unix and Mac OS X as well as building.